Synchronous Bone Metastasis From Multiple Myeloma and Prostate Adenocarcinoma as Initial Presentation of Coexistent Malignancies - Adrianzen Herrera, Diego Andres; Goldberg-Stein, Shlomit; Sankin, Alexander; Sarungbam, Judy; Sharma, Janaki; Gartrell, Benjamin A. (Frontiers in Oncology, 2018)
The radiographic appearance of bone metastases is usually determined by tumor histology and can be osteolytic, osteoblastic, or mixed. We present a patient with coexistent bone metastasis from multiple myeloma and prostate adenocarcinoma who exhibited synchronous bone involvement of both histologies within the same bone lesion, a rare phenomenon that has not been previously reported and led to atypical radiographic findings. The radiograph of a 71-year-old man with thigh swelling and pain demonstrated a lytic femoral lesion. Magnetic resonance imaging (MRI) confirmed a destructive process, but showed coexistent metaphyseal sclerosis. Multiple myeloma was suspected by demonstration of monoclonal gammopathy and confirmed by computed tomography (CT)-guided biopsy. Incidentally, CT demonstrated areas of sclerosis corresponding to T2 hypointensity on MRI. Further studies revealed osteoblastic spinal metastasis, prostate enhancement on CT and prostate-specific antigen (PSA) level of 90 ng/mL, concerning for concomitant prostate neoplasm. After endoprosthetic reconstruction, pathology of the femur identified both plasma cell neoplasm and metastatic prostate adenocarcinoma. An association between prostate cancer and multiple myeloma is hypothesized due to tumor microenvironment similarities and possible common genetic variations, however, coexisting bone metastases have never been reported. This unusual finding explains the discrepant imaging features in our patient and is evidenced that certain clinical situations merit contemplation of atypical presentations of common malignancies even if this leads to additional testing.